2023
DOI: 10.1002/hipo.23526
|View full text |Cite
|
Sign up to set email alerts
|

Reap while you sleep: Consolidation of memories differs by how they were sown

Abstract: Newly formed memories are spontaneously reactivated during sleep, leading to their strengthening. This reactivation process can be manipulated by reinstating learning-related stimuli during sleep, a technique termed targeted memory reactivation. Numerous studies have found that delivering cues during sleep improves memory for simple associations, in which one cue reactivates one tested memory. However, real-life memories often live in rich, complex networks of associations. In this review, we will examine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…The consolidation trajectory hypothesis, by Antony & Schechtman (2023), posits that sleep serves to reinforce goals formed during learning, such that if interconnected elements of a complex memory are learned harmoniously, they will be jointly promoted during sleep; if they are learned antagonistically, they will be pitted against each other during sleep 62 . One prior TMR study demonstrated that generating specific competitive dynamics during pre-nap learning modulated the impacts of reactivation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The consolidation trajectory hypothesis, by Antony & Schechtman (2023), posits that sleep serves to reinforce goals formed during learning, such that if interconnected elements of a complex memory are learned harmoniously, they will be jointly promoted during sleep; if they are learned antagonistically, they will be pitted against each other during sleep 62 . One prior TMR study demonstrated that generating specific competitive dynamics during pre-nap learning modulated the impacts of reactivation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The preceding results accord well with the qualitative results from our prior study examining retroactive effects (with a few exceptions, which we cover more extensively in the Discussion). One conclusion from these converging results could be that relatedness benefits memories in the retroactive and proactive case for similar reasons, namely that by virtue of increasing the likelihood of looking back and associating new learning with existing memories, it helps the connected memories survive due to being embedded in an integrated memory structure (Antony & Schechtman, 2023;Lee & Chen, 2022;Schlichting et al, 2015;Trabasso & Sperry, 1985). Our results here and earlier, as well as those from other recent studies showing that memory updating benefits from variables that improve contact between the past and present (e.g., Kemp et al, 2023;Wahlheim et al, 2020Wahlheim et al, , 2023Wahlheim & Zacks, 2019), support this idea.…”
Section: Comparing Retroactive and Proactive Memory Effectsmentioning
confidence: 99%